TEACHER PROBLEMS IN THE IMPLEMENTATASI KURIKULUM MERDEKA: LITERATURE STUDY - Rahayu, Jeni; Maghfiroh, Ana (Journal of Language, Education, Literature, and Culture, 2023)
Curriculum is a plan designed to facilitate the teaching and learning process under the guidance and responsibility of a school or educational institution, including educators. Currently the implemented curriculum is the Kurikulum Merdeka. Learning tools, determining learning objectives, and conceptualizing the delivery of material are some of the problems found in the study of this research literature. The purpose of this study is to discuss further the problematic Implementasi Kurikulum Merdeka. This study using the literature review method with 7 article reference data sourced from Google Schoolar. Component the subject matter of discussion: 1) kinds of teacher problems, 2) Solution of teachers problem to implemented Kurikulum Merdeka 3) kind of methods used in research, 4) Subject of the research. Then the results of these questions: 1) teacher problem were teacher's difficulties in converting learning outcomes (LO) into appropriate learning objectives, lack of literacy materials, lack of learning media and the teacher's creativity to make class interesting, a lot of categories assessments, the teacher's lack of understanding of technology. Solutions offered to research data include: 2) the solution were teachers are active in participating in training and seminars on the independent curriculum so that they have broader insights and provisions for implementing the independent curriculum, teachers and school parties collaborate with supporting parties in implementing the independent curriculum, teachers must have a willingness to learn to upgrade themselves and adapt to technology. 3) the researchers often used qualitative studies case, 4) the subject of the researchers were Elementary School Teachers.